2019
DOI: 10.1177/1073191118824660
|View full text |Cite
|
Sign up to set email alerts
|

The Interpersonal Needs Questionnaire: Statistical Considerations for Improved Clinical Application

Abstract: The interpersonal theory of suicide (ITS) has accumulated empirical support; however, less research has investigated the clinical utility of ITS constructs in suicide risk assessment. The current study sought to increase the clinical utility of the Interpersonal Needs Questionnaire (INQ), an assessment of thwarted belongingness (TB) and perceived burdensomeness (PB), among 318 adult psychiatric outpatients while considering statistical methodology (i.e., multicollinearity and partialling). Results emphasized P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 54 publications
(150 reference statements)
4
30
1
Order By: Relevance
“…Next, we provide an overview of an example of these categorical methods in the suicide literature. Mitchell et al (2020) tested thwarted belonging and perceived burden (continuous x variables) as predictors of desire for death and desire for suicide ( y ; coded 0 = no desire, 1 = some level of desire) among 318 psychiatric outpatients. To partially describe their results as they pertain to this paper (see Mitchell et al, 2020 for a complete description), they found a positive relation between thwarted belonging and desire for suicide (logit = 0.08, OR = 1.08, p < 0.001); however, to allow a more direct comparison of the OR s for thwarted belonging and perceived burden, they also conducted their analyses with z‐score transformed thwarted belonging and perceived burden scores.…”
Section: Review Of Logistic Regression and Its Clinical Utilitymentioning
confidence: 99%
See 4 more Smart Citations
“…Next, we provide an overview of an example of these categorical methods in the suicide literature. Mitchell et al (2020) tested thwarted belonging and perceived burden (continuous x variables) as predictors of desire for death and desire for suicide ( y ; coded 0 = no desire, 1 = some level of desire) among 318 psychiatric outpatients. To partially describe their results as they pertain to this paper (see Mitchell et al, 2020 for a complete description), they found a positive relation between thwarted belonging and desire for suicide (logit = 0.08, OR = 1.08, p < 0.001); however, to allow a more direct comparison of the OR s for thwarted belonging and perceived burden, they also conducted their analyses with z‐score transformed thwarted belonging and perceived burden scores.…”
Section: Review Of Logistic Regression and Its Clinical Utilitymentioning
confidence: 99%
“…Note that this standardized OR ( x is in SD units) is larger than the unstandardized OR ( x is in the scale of the measure) because of the change in the meaning of a one‐unit increase when standardizing x scores. To provide practical results that would allow clinicians to calculate and interpret the predicted probability of some level of suicidal desire from patients’ thwarted belonging scores, Mitchell et al (2020) provided predicted probability figures and noted that these figures were derived from the unstandardized logistic regression estimates because the unstandardized assessment scores would likely be used in clinical settings. They also offered sample interpretations of the predicted probability figures.…”
Section: Review Of Logistic Regression and Its Clinical Utilitymentioning
confidence: 99%
See 3 more Smart Citations